2012
DOI: 10.1002/sca.21033
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Measuring the Molecular Force of Lymphoma Pathological Cells Using Atomic Force Microscopy

Abstract: Summary: Atomic force microscopy (AFM) provides a new technology to visualize the cellular topography and quantify the molecular interactions at nanometer spatial resolution. In this work, AFM was used to image the cellular topography and measure the molecular force of pathological cells from B-cell lymphoma patients. After the fluorescence staining, cancer cells were recognized by their special morphological features and then the detailed topography was visualized by AFM imaging. The AFM images showed that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Here we imaged the cellular morphology of cancer cells from patients under the assistance of fluorescence recognition. We have previously used AFM to image the cancer cells assisted by CD20 fluorescence labeling (Li et al ., ), but the disadvantage of this method was that the CD20‐rituximab binding force cannot be measured on the cancer cells after CD20 fluorescence labeling.…”
Section: Resultsmentioning
confidence: 99%
“…Here we imaged the cellular morphology of cancer cells from patients under the assistance of fluorescence recognition. We have previously used AFM to image the cancer cells assisted by CD20 fluorescence labeling (Li et al ., ), but the disadvantage of this method was that the CD20‐rituximab binding force cannot be measured on the cancer cells after CD20 fluorescence labeling.…”
Section: Resultsmentioning
confidence: 99%
“…Rituximab was obtained from Chinese Affiliated Hospital of Military Medical Academy of Sciences. The procedure of linking rituximab molecules onto the AFM tips was according to the reference [29,30]. The NHS-PEG3500-MAL (JenKem Technology, Beijing, China) was used as linker molecules.…”
Section: Tip Functionalizationmentioning
confidence: 99%
“…The Gaussian fit of the force histograms indicated that the specific binding force (54738 pN) on the cancer cells was distinctly larger than the nonspecific binding force (21719 pN) on the red blood cells. We have previously investigated the CD20-rituximab binding forces on pathological samples [30], but the flaw of the previous researches was that the measurements were blind (we did not know whether the measurements were performed on cancer cells or healthy B cells, and thus the results were elusive). Here under the recognition of ROR1 fluorescence labeling, we can clearly discern the cancer cells and exactly perform the measurements on cancer cells.…”
Section: E X P E R I M E N T a L C E L L R E S E A R Cmentioning
confidence: 99%
“…Because of increasingly wider applications of AFM in life sciences, we now have a deeper understanding of physiological activities at the single-cell and single-molecule levels [36][37][38][39][40]. We can now obtain highresolution images of single membrane proteins and observe conformational changes.…”
Section: Challenge and Outlookmentioning
confidence: 99%